Cardiovascular response to stress in patients with drug-resistant epilepsy: preliminary data - Lozano-García, Alejandro; Catalan, Judit; Hampel, Kevin; Villanueva, Vicente; Gonzalez-Bono, Esperanza; Cano-Lopez, Irene (Anales de Psicología / Annals of Psychology, 2021)
Stress is a risk factor for cardiovascular diseases in the general population. Epilepsy has been considered a suitable model of chronic stress with a higher incidence of cardiovascular mortality than the general population. This study provides preliminary data about cardiovascular response to a cognitive stressor and a neuropsychological assessment in patients with epilepsy. It also explores the relationship between cardiovascular response and cognitive performance, depending on the side of seizure focus. Thirty-five patients with drug-resistant epilepsy, 17 with epileptogenic area (EA) in the left hemisphere (LH) and 18 with EA in the right hemisphere (RH), underwent a cognitive stressor and a neuropsychological assessment. The cardiovascular response was recorded throughout both conditions. Results showed that a long-lasting neuropsychological assessment was capable of producing a hemisphere-modulated cardiovascular response with heart rate (HR) decreases (and R-R interval increases) more pronounced in the LH patients than in the RH patients at the post-assessment period (p = .05 and p = .01, respectively). The hemisphere of EA moderated the relationship between cardiovascular response and cognitive performance (for all, p < .03). Our findings may have clinical implications from a preventive perspective since the EA hemisphere may be a relevant factor for coping with stress in people with drug-resistant epilepsy.